Vascularized Composite Allograft Versus Prosthetic for Reconstruction After Facial and Hand Trauma: Comparing Cost, Complications, and Long-term Outcome - Noel, Olivier F; Dumbrava, Mihai G; Daoud, Deborah; Kammien, Alexander J; Kauke-Navarro, Martin; Pomahač, Bohdan; Colen, David (Annals of plastic surgery, 2024)
In the past decade, vascularized composite allotransplantation (VCA) has become clinical reality for reconstruction after face and hand trauma. It offers patients the unique opportunity to regain form and function in a way that had only been achieved with traditional reconstruction or with the use of prostheses. On the other hand, prostheses for facial and hand reconstruction have continued to evolve over the years and, in many cases, represent the primary option for patients after hand and face trauma. We compared the cost, associated complications, and long-term outcomes of VCA with prostheses for reconstruction of the face and hand/upper extremity. Ultimately, VCA and prostheses represent 2 different reconstructive options with distinct benefit profiles and associated limitations and should ideally not be perceived as competing choices. Our work adds a valuable component to the general framework guiding the decision to offer VCA or prostheses for reconstruction after face and upper extremity trauma.
Keywords: Facial Injuries; štěpy z kompozitní tkáně; Plastic Surgery Procedures; lidé; horní končetina; Vascularized Composite Allotransplantation; Upper Extremity; Composite Tissue Allografts; vaskularizovaná kompozitní alotransplantace; zákroky plastické chirurgie; poranění obličeje; Humans